Halal Business Education for Non-Muslim MSMEs: Safeguarding Muslim Consumer Rights and Social Cohesion in Indonesia - Sugeng Santoso; Muhammad Sulthon Zulkarnain (Peradaban Journal of Religion and Society, 2026)
This study examines the urgency of halal business education for non-Muslim-owned MSMEs as a social mechanism to safeguard Muslim consumer rights within the context of Indonesia’s pluralistic society. Employing a qualitative method based on library research with a critical analysis of contemporary literature on public ethics and economic sociology, this research positions halal business education as a cross-religious social education. This framework allows the majority's religious values to function effectively within the economic sphere without requiring theological internalization from non-Muslim actors. Diverging from previous studies that tend to view halal solely as a regulatory instrument, this study offers a conceptual enrichment by linking halal education to consumer rights protection and social cohesion. The findings indicate that halal business education plays a significant role in reducing resistance among non-Muslim MSMEs and transforming halal from a religious identity symbol into a rational public ethic. This education proves to be a mechanism for reducing the disparity in majority-minority relations by positioning non-Muslim MSMEs as active subjects in market fulfillment. The primary contribution of this research lies in the formulation of an inclusive halal education framework that expands the halal discourse from normative compliance toward an instrument of social integration in a multicultural society. Studi ini mengkaji urgensi pendidikan bisnis halal bagi UMKM milik non-Muslim sebagai mekanisme sosial untuk menjamin hak konsumen Muslim dalam konteks masyarakat plural Indonesia. Menggunakan metode kualitatif berbasis studi kepustakaan dengan analisis kritis terhadap literatur mutakhir mengenai etika publik dan sosiologi ekonomi. Penelitian ini memosisikan pendidikan bisnis halal sebagai edukasi sosial lintas agama yang memungkinkan nilai keagamaan mayoritas hadir secara fungsional dalam ruang ekonomi tanpa menuntut internalisasi teologis dari pelaku non-Muslim. Berbeda dengan penelitian sebelumnya yang cenderung menempatkan halal semata sebagai instrumen regulatif, studi ini menawarkan pengayaan konseptual dengan menautkan pendidikan halal pada isu perlindungan hak konsumen dan kohesi sosial. Hasil kajian menunjukkan bahwa pendidikan bisnis halal berperan signifikan dalam mereduksi resistensi UMKM non-Muslim dan mentransformasi halal dari simbol identitas menjadi etika publik yang rasional. Pendidikan ini terbukti menjadi mekanisme reduksi ketimpangan relasi mayoritas–minoritas dengan menempatkan UMKM non-Muslim sebagai subjek aktif dalam pemenuhan pasar. Kontribusi utama penelitian ini adalah perumusan kerangka pendidikan halal inklusif yang memperluas diskursus halal dari kepatuhan normatif menuju instrumen integrasi sosial dalam masyarakat multikultural.